(untitled) (Kanun: Jurnal Undang-undang Malaysia, 2022)
The sale of counterfeit goods is an illegal act in which dealers place original manufacturer trademarks on non-genuine goods. This offense is often brought to the court under the Copyright Act 1987, the Trade Marks Act 1976, and the Trade Descriptions Act. However, despite having all sorts of enforcement of laws to ensure that this offense is eradicated, there are still countless cases of sales of counterfeit goods that are detrimental to society. This study was conducted to examine the effectiveness of the existing legal frameworks and the standard operating procedure in Malaysia that governs this issue. Through this study, specific legal frameworks were identified to prevent the reoccurrence of this offense. The differences in the enforcement of law between Malaysia and the United Kingdom as well as suggestions for improvement were also discussed in this article. The result found that existing legal enforcement is effective enough. However, if the enforcement were to be further improved, such as by creating a comprehensive act and emulating a settlement system in the United Kingdom that offers the most appropriate advice and solution to complainants online, this effort can certainly reduce the number of cases of counterfeit goods sold in Malaysia more effectively. Keywords: Law enforcement, sale of counterfeit goods, Copyright Act 1987, Trade Marks Act 1976, Trade Descriptions Act, United Kingdom Full text: PDF